First Study on Chromosomal Feature and NORs Localization of the Yellow-Spotted Keelback Snake, Fowlea Flavipunctatus (Squamata, Natricinae) in Thailand - Donbundit ์Nattasuda (Food Agricultural Sciences and Technology, 2020)
The first report on chromosome of the Yellow-spotted keelback snake (Fowlea flavipunctatus) family Colubridae (Natricinae), from Khon Kaen Province, Thailand, was investigated using classical cytogenetic approaches. The mitotic chromosomes were demonstrate prepared directly from the bone marrow cells of three male and four female specimens after in vivo colchicine treatment. The results that the diploid chromosome number was 2n=42, while the fundamental number (NF) was 58 in both male and female. The types of macrochromosome were six large metacentric, two large acrocentric, four small metacentric and four small telocentric chromosomes, and 24 microchromosomes (2m+22t). It was found that nucleolar organizer regions (NORs) located on subtelomeric position of p-arm of macrochromosomes pair 4. The sex chromosome system was ZW. The karyotype formula for F. flavipunctatus is as follows: 2n (42) = Lm6 + La2 + Sm4 + St4 + 24 microchromosomes + sex chromosomes (ZW).